Psikoedukasi Kontrol Diri dengan Metode Role Play untuk Mencegah Kenakalan Remaja pada Remaja RW 04 Kelurahan Bandarharjo - Btari Carlinda Bachri; Ayyash Muhammad Azman; ME Nanda Maulana; Muhammad Fathinudin Azhar; Muhammad Arief Zuliyan; Fika Nadia Tirta Maharani (ABISATYA : Journal of Community Engagement, 2026)
Juvenile delinquency is a social issue that continues to draw attention, particularly in Bandarharjo Subdistrict, where the community has raised concerns about fights, alcohol consumption, and drug distribution among adolescents. This study aims to encourage adolescents to practice self-control behaviors in order to prevent themselves from engaging in negative activities through non-training psychoeducation using interactive lectures and role play. The program involved 20 adolescents aged 12–15 years in RW 04 Bandarharjo Subdistrict. The results of this activity showed that participants were able to understand the consequences of juvenile delinquency and the importance of self-control in resolving conflicts without violence. Through role play, participants were also able to practice assertively refusing invitations to engage in delinquent behaviors such as fighting and smoking. This program contributes to the prevention of juvenile delinquency in Bandarharjo Subdistrict. Future studies are recommended to involve a larger number of participants and adopt more structured measurements, such as pre-tests and post-tests, to more accurately assess the program’s effectiveness.